Relationship of Social-Emotional Learning, Resilience, Psychological Well-Being, and Depressive Symptoms with Physical Activity in School-Aged Children - Evan Belaire; Fawzi Mualla; Lucas Ball; Iris Ma; Debra Berkey; Weiyun Chen (MDPI AG, 2024)
Background: This study investigated the association of psychological well-being (PWB), resilience, depressive symptoms, and social-emotional learning (SEL) with physical activity (PA) in school-aged children. The objective was to understand how these psychosocial factors influence PA levels and identify gender-specific differences in these relationships. Methods: This cross-sectional study involved 534 fourth grade and sixth grade students from eight schools in the Midwest region of the United States, with data collected through a Qualtrics survey. Multiple linear regression models were used to analyze the data, with gender-specific analyses conducted to identify differences between boys and girls. Results: The models indicated that all psychosocial factors taken together are significantly associated with PA (F = 26.937, p < 0.001). Of the factors, PWB and resilience were associated with higher PA individually for the total sample (β = 0.383, p = 0.001; β = 0.146, p = 0.005). A gender-specific analysis revealed that all factors collectively were significantly associated with PA in boys and girls (F = 15.846, p < 0.001; F = 6.869, p < 0.001). Individually, PWB and resilience were significantly associated with PA in boys (β = 0.358, p = 0.001; β = 0.171, p = 0.013), while only PWB was significantly associated with PA in girls (β = −0.355, p = 0.001). Conclusions: This study highlights the necessity of promoting resilience and psychological well-being through structured physical activities, aiming to reduce the risk of obesity and improve mental health among children. Future research should consider longitudinal designs and objective measures to further elucidate these relationships and inform effective educational strategies.